DIPG-12. CHARACTERIZING THE ROLE OF PPM1D MUTATIONS IN THE PATHOGENESIS OF DIFFUSE INTRINSIC PONTINE GLIOMAS (DIPGs). (23rd April 2019) - Khadka, Prasidda; Reitman, Zachary J; Buchan, Graham; Hartley, Rachel; Bear, Heather; Georgis, Yohanna; Jarmale, Spandana; Schoolcraft, Kathleen; Miller, Peter; Stiles, Charles D; Chowdhury, Dipanjan; Haas-Kogan, Daphne; et al.
Abstract: Diffuse Intrinsic Pontine Gliomas (DIPGs) are universally fatal. Effective treatments are desperately needed. DIPGs harbor histone K27M mutations ( H3F3A or HIST1H3B ) and also alterations that lead to growth factor receptor activation (such as PDGFRA amplification). We and others have found recurrent truncating PPM1D mutation ( PPM1Dtr ) in up to 20% of all DIPGs, and they are mutually exclusive with TP53 mutations. We hypothesized that PPM1D mutations are sufficient to induce oncogenesis and necessary for DIPG proliferation, and therefore represent a therapeutic target. To assess the ability of PPM1Dtr to cooperate with H3F3A K27M and PDGFRA activation to drive DIPG tumorigenesis, we overexpressed PPM1Dtr in mouse neural stem cells (mNSCs), along with the contextual H3F3A K27M and PDGFRA D842V activating mutations. Overexpression of PPM1Dtr conferred a significant proliferative advantage to mNSCs in the presence of H3F3A K27M and PDGFRA D842V overexpression. PPM1Dtr overexpression strongly suppressed g-H2AX formation and apoptosis in response to treatment with ionizing radiation. Overexpression of PPM1Dtr along with H3F3A K27M and PDGFRA D842V was also sufficient to induce tumorigenesis in vivo . Furthermore, CRISPR-Cas9 mediated ablation of PPM1D in a patient-derived PPM1D mutant DIPG cell line significantly impaired the growth of these cells, suggesting that PPM1D is a critical dependency in DIPG. Taken together, our study shows that PPM1Dtr is both an oncogene and dependency in PPM1D mutant DIPG, and represents a potential therapeutic target.